Antibody-based delivery of interleukin-9 to neovascular structures: Therapeutic evaluation in cancer and arthritis. Issue 8 (April 2021) - Gouyou, Baptiste; Ongaro, Tiziano; Cazzamalli, Samuele; De Luca, Roberto; Kerschenmeyer, Anne; Valet, Philippe; Villa, Alessandra; Neri, Dario; Matasci, Mattia
Interleukin-9 is a cytokine with multiple functions, including the ability to activate group 2 innate lymphoid cells, which has been postulated to be therapeutically active in mouse models of arthritis. Similarly, interleukin-9 has been suggested to play an important role in tumor immunity. Here, we describe the cloning, expression, and characterization of three fusion proteins based on murine interleukin-9 and the F8 antibody, specific to the alternatively spliced EDA domain of fibronectin. EDA is strongly expressed in cancer and in various arthritic conditions, while being undetectable in the majority of healthy organs. Interleukin-9-based fusion proteins with an irrelevant antibody specific to hen egg lysozyme served as negative control in our study. The fusion proteins were characterized by quantitative biodistribution analysis in tumor-bearing mice using radioiodinated protein preparations. The highest tumor uptake and best tumor:organ ratios were observed for a format, in which the interleukin-9 moiety was flanked by two units of the F8 antibody in single-chain Fv format. Biological activity of interleukin-9 was retained when the payload was fused to antibodies. However, the targeted delivery of interleukin-9 to the disease site resulted in a modest anti-tumor activity in three different murine models of cancer (K1735M2, CT26, and F9), while no therapeutic benefit was observed in a collagen induced model of arthritis. Collectively, these results confirm the possibility to deliver interleukin-9 to the site of disease but cast doubts about the alleged therapeutic activity of this cytokine in cancer and arthritis, which has been postulated in previous publications.